Britain's youngest implant patients? – A Case Series of implant treatment in children with ectodermal dysplasia. (17th March 2020) - Clarke, L.; Bowyer, L.; Noone, J.; Stevens, C.; Yates, J.; Ashley, M.
Abstract: Ectodermal dysplasia is a hereditary disorder that is characterised by abnormalities in the development of embryologically derived ectodermal tissues and structures. Many patients with this condition can present with oligodontia or anodontia. Subsequently, this can lead to aesthetic and functional problems that can have negative effects on self‐esteem, self‐image and overall quality of life. Therefore, for this group of patients, there is a demand for prosthetic treatment in early childhood that is effective in managing their specific issues. This case series presents a method of prosthetic rehabilitation that uses dental implant‐retained overdentures for two paediatric patients with ectodermal dysplasia. We discuss the treatment options and limitations of conventional removable prostheses for these patients, and the rationale for implant placement. Furthermore, we discuss the significance of the psychological well‐being of the child and the positive effects that this treatment can have during their crucial early years of development and school years. Currently, there is limited evidence available for the use of dental implants in children. Thus, a multi‐disciplinary team approach with appropriate planning and parental involvement is essential for successful outcomes.